The Dilemma Caused by Delusional Defendants - Collins, David (Victoria University of Wellington Law Review, 2015)
This article explains the dilemmas that arise when a defendant, who is prone to delusional episodes but nevertheless fit to stand trial, elects to exercise the right to represent themself. It examines the background to the criteria for determining if a defendant is fit to stand trial under the Criminal Procedure (Mentally Impaired Persons) Act 2003, and then analyses the way those criteria have been interpreted in New Zealand. The difficulties caused by the New Zealand approach are then analysed in more detail by reference to the leading 2008 Supreme Court case of Cumming v R, which involved a delusional defendant who represented himself and who was subsequently found to have been unfit to stand trial.